The Effect of Nano Liquid Food Formula Made from Catfish and Moringa Flours on Oxidative Stress and Reduction of Burn Size in Rats: Efek Makanan Formula Cair Nano Berbahan Tepung Lele dan Kelor Terhadap Stres Oksidatif dan Pengurangan Luas Luka Bakar pada Tikus - Utari Yunitaningrum; Clara M. Kusharto; Katrin Roosita (Universitas Airlangga, 2023)
The high catabolism and inflammatory responses due to the burn injury can affect the increase of free radicals resulting in oxidative stress condition that delays the healing process of wounds. Providing protein can help to improve protein loss during catabolism, as for antioxidants, they prevent the occurrence of oxidative stress situation. One product of protein and antioxidants source that have been developed is a liquid food formula made from Catfish and Moringa flour which were processed using nanotechnology. This study aims to analyze the effect of liquid food formula made from Catfish and Moringa flour processed using nanotechnology on Sprague Dawley rats with burn injury, especially on malondialdehyde levels and reduction in wound area. The design of this study was an experimental study with 6 experimental groups, namely rats with aquadest intervention (K), 15% liquid food formula (MCB 15), 30% liquid food formula (MCB 30), 15% nano liquid food (MCN 15), and 30% nano liquid food (MCN 30) that given for 14 days. The One Way ANOVA test indicated that there was no significant difference in malondialdehyde levels among all experimental groups. However, the highest decrease in malondialdehyde levels occurred in the MCN 30 group. Moreover, the MCN 30 group also showed the highest reduction in the wound area and was significantly different from the control group, MCB 15, MCN 15, and MCK 30, but didn’t show a significant difference from the MCB 30 group based on the One Way ANOVA test and a further test of Duncan.